Evolution of Skin during Rehabilitation for Elephantiasis Using Intensive Treatment - Henrique Jose Pereira de Godoy; Ricardo Budtinger Filho; Maria de Fatima Guerreiro Godoy; José Maria Pereira de Godoy (Case Reports in Dermatological Medicine)
The objective of this study is to describe the evolution of the skin during rehabilitation for elephantiasis using intensive treatment. We report on the case of a 55-year-old patient with a seven-year history of leg edema. The patient reported that it began with repeated outbreaks of erysipelas over several years. One leg evolved with significant edema leading to an inability to ambulate and for about one month the patient said that he could not get out of bed. Moreover the patient was obese weighing 130 kilos and with a BMI of 39. Intensive treatment was performed over three weeks resulting in a significant reduction in limb volume. The treatment consisted of Mechanical Lymphatic Therapy (RAGodoy), Cervical Lymphatic Stimulation (Godoy & Godoy technique), and a custom-made inelastic stocking of a grosgrain textile. What caught the attention during therapy were the open wounds resulting from fragmentation of the plaque as the edema reduced; the plaque was about 0.5 cm thick. As the treatment evolved the plaque disappeared and the wounds healed. The limb size decreased by more than 80% in three weeks after which the patient began to be treated in an outpatient setting with ambulation using a grosgrain stocking.